Role of capillary blood glucose in the control of type 2 Diabetes mellitus (Research, Society and Development, 2021)
Introduction: Diabetes mellitus (DM) is a pathology characterized by a control and disturbance of intermediate metabolism, especially with regard to the absorption and activity of carbohydrates. It represents a serious public health problem worldwide, indicators reveal that one of the main causes of cardiovascular disease in the Latin American continent is diabetes. Thus, the control of DM and the prevention of its diseases are necessary. Objective: The study aimed to describe the role of capillary glycemia in the treatment of type 2 diabetes mellitus. Material and Methods: This study has as methodology the integrative review model of bibliography, classified as analytical and with a qualitative approach. With the searches in the databases, the total number of articles and academic papers that were identified in the LILACS database, totaling 36 and for the search platform of the Scientific Electronic Library Online (SciELO), a total of 19 articles were found. Results and discussion: capillary glycemia allows people who have diabetes to have greater control over blood glucose values, preventing episodes of hypoglycemia because of insulin use, helping to understand how food, stress, emotions and physical exercise alter blood glucose levels and also helps define the correct dose of insulin to be administered. Conclusion: Therefore, the importance of capillary glycemia in the verification of blood glucose levels in the control and treatment of patients with type 2 diabetes is concluded.